Cannabis Use and Emotional Awareness Difficulties in Adolescents with Co-Occurring Substance Use and Psychiatric Disorders. (15th April 2020) - Micalizzi, Lauren; Brick, Leslie A.; Thomas, Sarah A.; Wolff, Jennifer; Esposito-Smythers, Christianne; Spirito, Anthony
Abstract: Background: Assessing predictors of cannabis use following adolescent substance use treatment may inform essential treatment elements to be emphasized before discharge. Adolescents with low emotional awareness may have limited resources for identifying and overcoming negative emotions, and therefore, use cannabis to regulate emotions. Purpose/objectives: The purpose of this study was to test the hypothesis that emotional awareness difficulties are associated with increased cannabis use across the transition out of substance use treatment. This hypothesis was investigated by applying an autoregressive random-intercept cross-lagged panel-modeling framework to test the fit of alternative models and inform hypotheses about directional associations between cannabis use and emotional awareness difficulties over time. Methods: Participants were 110 adolescents with co-occurring disorders and their families participating in an intensive home-based treatment trial. Adolescents reported on past 7-day cannabis use and difficulties in emotional awareness at baseline and three follow-up assessments across 12 months. Results: At baseline, 54% of the sample reported past-week cannabis use. A directional effect was supported such that difficulties with emotional awareness at 3 months' post-baseline, which corresponded to the approximate end of the treatment program, were associated with increased cannabis use at 6 months' post-baseline, controlling for the stability of cannabis use, and emotional awareness over time. Cannabis use, however, was not associated with subsequent difficulties in emotional awareness (i.e., effects in the opposite direction were not supported). Conclusions/Importance: Emotional awareness difficulties toward the end of a course of intensive outpatient treatment may be associated with increased cannabis use after the completion of treatment.